Disable perception towards rail transportation in Kuala Lumpur - Azlan, Nur Nadhirah; Murat, Nur Fatin Farhanah; Melan, Mustakim (Universiti Utara Malaysia, 2019)
The objective of this paper is to identify the relationship between customer perception, facilities and service that might impact to the disability that using rail transportation in Kuala Lumpur. The study a covers a disable population of rail transportation in Kuala Lumpur. A total of respondent 284 respondent participated in this paper. Pearson correlation was performed to analyze used to study the significant differences of respondent between demographic factors. Goodness of measure like pearson correlation analysis used to examine disable perception towards rail transportation in Kuala Lumpur. The results show that there are significant and not significant relationship exists between the variables. Customer Satisfaction Index (CSI) has been used to assess the measurement model on a sample of disability passengers that being using the rail transportation in Kuala Lumpur as their regular transportation. The measurement model assessment has been involves oblique the validity, internal consistency and the discriminant validity of the identified factors and to measure the items. The result that being shows will identified all of the factors to fulfilled the discriminant validity and oblique of the research